Police and Private Security Partnership in Crime Prevention, A Study of Nairobi County - Kipkorir, Ombachi (2021)
With regard to the provision of security services in Kenya, Police and private security function in a mutually exclusive manner. However, it apparent that is essential to develop a formal partnership relationship, because both have several shared goals. Additionally, the private security industry also plays a significant protective role in the country. The study sought to investigate the reality of partnership between the police and the private security in Kenya. It sought to achieve this by examining the existence of any level of partnership between the private security and police in provision of security. The study also sought to establish the existing partnership between the private and public security, especially in places of common protection of public gatherings, information exchange, security and transport of money, information, and private security handing over suspected offenders to the police and how the challenges facing both private and public security providers can be curbed to enhance security. This is based on the premise that conditions for effective cooperation between the police and private security providers are not yet well developed. This study examined how co-operation in crime prevention and policing could be realized and made beneficial to all role players within the framework of a public-private security partnership. The research used both qualitative and qualitative approaches in collecting, as well as analyzing data. Additionally, both secondary and primary data were collected, with primary data being collected by use of questionnaire and interview schedule. The primary data was collected in Nairobi which was purposely sampled for its large intensity of criminal activities and security providers, both private and public. The data was analyzed using statistical package for social sciences (SPSS). The study provides deeper knowledge of local security dynamics and gives an insight into measures that could be taken to harness the energies and potentials of police and private security partnership. It also serves as a basis for future research into the country’s overall strategy for providing security whilst contributing to the existing body of literature to address scarcity of data in this research area in Kenya. Keywords: Police, Private Security, Partnership, Crime Prevention DOI: 10.7176/PPAR/11-1-01 Publication date: January 31st 202